Utilizing Films in EFL Classroom for Learning Speaking: A Study at English Major - Fakhrurriana, Ria; Rahmaddian, Aldy Muria; Aunillah, Hilwah Nur; Herdina, Griselda (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2024)
Nowadays, speaking skills can be learned through various techniques and resources. One of them is watching films. Watching films using English subtitles is one of the best ways to present authentic content because it combines audio and visuals This research purposed to know how are English major students’ perceptions towards watching English films to develop speaking skills. The participants were 30 students in the sixth semester of the English Education Department in IAIN Kediri. For data collection, a questionnaire consisting of ten questions was employed to gather information about the respondents' background, perceptions regarding watching English films, and their level of agreement with respect to English films. The descriptive method is utilized because the data analysis is presented in a descriptive manner. According to the percentage of the finding, there are (75,8%) of students chose the option Agree, while there is (0%) of students chose the option Strongly Disagree in all the items. The survey shows the highest answer from respondents is “agree” about their perceptions towards watching English films to develop speaking skills. Based on the results of respondents’ perceptions, researchers can conclude that English film has good perceptions and has good influences in developing students’ speaking skills.